Native language interference in learning English as a foreign language: an analysis of written material produced by spanish speaking students in Senior High school classes. - Baque Zambrano, Sandra Merly (2010)
Interference among languages exists and the goal of this project is to explain the difficulties in the acquisition of English as a foreign language in our own context due to native Language interference. I have chosen a place located on the north-est area of the Manabí Province, within the Union y Progreso community near to La Bramadora which belongs to El Carmen Canton. The sample has been extracted out of twenty senior students from “Juan Pablo II” “Fe y Alegría” Private School, who were requested to write four different kinds of written text. In order to conduct this research, it was necessary to use several scientific methods, as bibliographic methods and instruments including direct observation, questionnaires, and cards, the analytic and descriptive methods were used for the interpretation of the data gathered through the applied activities such as a composition, a story, an essay and a quiz. This research evidences that most of learners showed to have native language interference having errors like double negation, omission of the subject pronoun, incorrect use of the article “the”, pluralization and position of adjectives, omission of auxiliaries, use of false cognates and invented words.